Nutritional status among Malay preschool children in private kindergarten in Shah Alam / Fadhilah Lamun @ Jailani and Siti Suhara Ramli - Lamun @ Jailani, Fadhilah; Ramli, Siti Suhara (2006)
A cross-sectional study was carried out to assess the nutritional status of preschool children in Shah Alam, Selangor. Ten private kindergartens were chosen by simple random sampling. A total of 266 Malay preschoolers comprising 136 boys and 130 girls aged between 3 to 6 years old and their mothers participated in this study. A set of structured questionnaire was used to obtain information on demographic characteristics, anthropometric measurements and food habits of the preschoolers. Anthropometric measurement such as weight and height were measured TANITA weighing scale and SECA body meter respectively. The anthropometric measurements were then compared with National Centre for Health Statistics (NCHS) reference. The anthropometric assessments indicated that 9.8% (n=26) of the preschoolers were underweight, 9.8% (n=26) overweight, 8.6% (n=23) stunted and 3.8% (n=10) wasted when compared with NCHS reference. Food frequency data indicated that food most frequently taken by the children were rice, bread and fish, whereas egg, milk, carrot, banana and traditional Malaysian kuih were moderately consumed by the preschool children. Based on the result obtained, it demonstrated that respondents' mother's nutritional knowledge was satisfactory. Correlation analysis showed that there was no significant relationship between anthropometric index (weight for age, height for age and weight for height) and socio-demographic factors, food variety score and mother nutritional knowledge. As a conclusion, the nutritional status of these preschool children was satisfactory. However, result demonstrates an increasing prevalence of overweight among studied preschoolers. The importance of health and nutrition monitoring among preschoolers should be emphasized by the relevant authorities.